Antidepressants Usage and Risk of Pneumonia Among Elderly Patients With the Parkinson's Disease: A Population-Based Case-Control Study - Kuo, Wei-Yin; Huang, Kuang-Hua; Kuan, Yu-Hsiang; Chang, Yu-Chia; Tsai, Tung-Han; Lee, Chien-Ying (Frontiers in Medicine, 2022)
Patients with Parkinson’s disease (PD) are associated with a higher risk of pneumonia. Antidepressants exert an anticholinergic effect in varying degrees and various classes of antidepressants also can produce different effect on immune function. The relationship between the risk of pneumonia and the use of antidepressants among elderly PD patients is unknown. The study investigated the risk of pneumonia associated with the use of antidepressants in elderly patients with PD. This case-control study was based on data from the longitudinal health insurance database in Taiwan. We analyzed the data of 551,975 elderly patients with PD between 2002 and 2018. To reduce the potential confounding caused by unbalanced covariates in nonexperimental settings, we used propensity score matching to include older patients without pneumonia to serve as the comparison. The antidepressants in the study included tricyclic antidepressants (TCAs), monoamine oxidase inhibitors (MAOIs), selective serotonin reuptake inhibitors (SSRIs), serotonin norepinephrine reuptake inhibitors (SNRIs). The conditional logistic regression was used to investigate the association between antidepressants and pneumonia. Control variables in the study included sex, age, income level, urbanization, CCI score and comorbidities related to pneumonia. In terms of TCAs users, compared with patients not receiving TCAs, current users had a lower risk of incident pneumonia (aOR=0.86, 95% CI=0.82-0.90), and recent users (aOR=0.83, 95% CI=0.80-0.87). In terms of MAOIs users, current users had a lower risk of incident pneumonia (aOR=0.88, 95% CI=0.83-0.93), recent users (aOR=0.89, 95% CI=0.85-0.93). In terms of SSRIs users, current users had a higher risk of incident pneumonia (aOR=1.13, 95% CI=1.01-1.17), recent users (aOR=1.01, 95% CI=1.06-1.13), and past users (aOR=1.19, 95% CI=1.17-1.21). In terms of SNRIs users, past users had a higher risk of incident pneumonia (aOR=1.07, 95% CI=1.03-1.10). The incident pneumonia is associated with the use of individuals of different classes of antidepressants. The use of TCAs (including amitriptyline and imipramine) had a lower odds of incident pneumonia. The use of MAOIs (including selegiline and rasagiline) had a lower odds of pneumonia during recent use. The use of SSRIs (including fluoxetine, sertraline, escitalopram, paroxetine and citalopram) and SNRIs (including milnacipran and venlafaxine) had a higher odds of incident pneumonia.